Vitamin C and Total Sugar Content Characterization on 31 Accessions of Banana Collection of Banana Germplasm Plants of Yogyakarta - Indrasari, Siti Dewi; Kristamtini, Kristamtini; Wiranti, Endang Wisnu (Biology, Medicine, & Natural Product Chemistry, 2017)
Banana is one of the tropical fruits that people like because it tastes good and contains good nutritional value that beneficial for health.Ã‚Â  The content of vitamin C and total sugar are an important character to complete the morphological characterization of banana accession that can be utilized by breeders in choosing accession as parent. The study aimed to determine the content of vitamin C and total sugar on 31 accessions of banana collection of Banana Germplasm Plants of Yogyakarta. The research was conducted at Banana Germplasm Plantation and Laboratory of Agricultural Technology Production of Gadjah Mada University, Yogyakarta from January to December 2016. The results indicated that 31 banana accessions showed their susceptibility to vitamin C content 60.42 + 39.22 mg / 100 g and total sugar 22.06 + 16.01%. High standard deviation values indicate the large diversity of banana accessions that were characterized, indicating that the accessions of each characterized banana were separate accessions of one another.